Caracterización de propiedades físico-mecánicas de rocas ígneas utilizadas en obras de infraestructura - Navarrete, M.; Martínez Molina, W.; Alonso-Guzmán, E. M.; Lara-Gómez, C.; Bedolla-Arroyo, J. A.; Chávez, H.; Delgado, D.; Arteaga, J. C. (Revista ALCONPAT, 2013)
Stone materials are currently used in almost all building processes and because of this they perform different tests can be both physical and mechanical , in these, the load test regulated by ASTM D 5731 , describes the use of the instrument Point Load to determine the mechanical strength unhewn rocks , with approximate size of 4 inches in diameter , determining mechanical properties with high reliability and ease , it is economical method because the team can take the site or (bank) quarry , not necessary till the specimens. If further tests are physical and current humidity, absorption, density, specific gravity, these results help to better understand the mechanical behavior of the stone, being able to achieve an economy, as in the preparation of concrete, hydraulically and asphalt. This paper also compares the physical and mechanical properties of materials banks in the region of Morelia, Michoacan, Mexico